Correlating electroconvulsive therapy response to electroencephalographic markers: Study protocol - Subramanian, Subha; Labonte, Alyssa K.; Nguyen, Thomas; Luong, Anhthi H.; Hyche, Orlandrea; Smith, S. Kendall; Hogan, R. Edward; Farber, Nuri B.; Palanca, Ben Julian A.; Kafashan, MohammadMehdi; , CET-REM Study Group; Gupte, Gaurang; et al. (Frontiers in Psychiatry, 2022)
Introduction Electroconvulsive therapy (ECT) is an effective intervention for patients with major depressive disorder (MDD). Despite longstanding use, the underlying mechanisms of ECT are unknown, and there are no objective prognostic biomarkers that are routinely used for ECT response. Two electroencephalographic (EEG) markers, sleep slow waves and sleep spindles, could address these needs. Both sleep microstructure EEG markers are associated with synaptic plasticity, implicated in memory consolidation, and have reduced expression in depressed individuals. We hypothesize that ECT alleviates depression through enhanced expression of sleep slow waves and sleep spindles, thereby facilitating synaptic reconfiguration in pathologic neural circuits. Methods Correlating ECT Response to EEG Markers (CET-REM) is a single-center, prospective, observational investigation. Wireless wearable headbands with dry EEG electrodes will be utilized for at-home unattended sleep studies to allow calculation of quantitative measures of sleep slow waves (EEG SWA, 0.5–4 Hz power) and sleep spindles (density in number/minute). High-density EEG data will be acquired during ECT to quantify seizure markers. Discussion This innovative study focuses on the longitudinal relationships of sleep microstructure and ECT seizure markers over the treatment course. We anticipate that the results from this study will improve our understanding of ECT.